Predictive factors of complications and visual outcomes after pediatric cataract surgery: A single referral center study from Türkiye - DERİCİOĞLU, VOLKAN; SEVİK, MEHMET ORKUN; BAĞATUR VURGUN, ELİF; ÇERMAN, EREN (My University, 2023)
Objectives: To evaluate the predictive factors of complications and visual acuity outcomes in pediatric cataract patients. Materials and Methods: This retrospective, observational clinical study included 80 eyes of 50 patients treated for pediatric cataracts between 2010 and 2020. The eyes were divided into Group I (congenital cataracts, n=38) and Group II (developmental cataracts, n=42). Group II was also divided into Group IIA (aphakic, n=21) and Group IIB (pseudophakic, n=21). The effects of the age, laterality, cataract morphology, intraocular lens implantation, preoperative nystagmus/strabismus, and intraoperative anterior hyaloid rupture on complications and final best-corrected visual acuity (BCVA; logMAR) were evaluated. Results: The median (interquartile range) age and follow-up time were 28 (5-79) months and 60 (29-84) months, respectively. There was a significant difference in mean final BCVA between Group I (0.79±0.46) and Group II (0.57±0.51) (p=0.047); however, no difference was observed between Group IIA and Group IIB (p=0.541). Having congenital cataract (p=0.045), preoperative nystagmus/strabismus (p=0.042), total/ mature cataract (p<0.001), and postoperative complications (p=0.07) were significantly associated with final BCVA. However, in multivariate analysis, only total/mature cataract (β: 0.52, p<0.001) and having any complication (β: 0.24, p=0.018) were associated with final BCVA. Congenital cataract and intraoperative anterior hyaloid rupture were the only significant risk factors of postoperative complications on univariate (p=0.027 and p=0.003, respectively) and binary logistic regression analysis (odds ratio [OR]: 2.95 [95% confidence interval: 1.07-8.15], p=0.036 and OR: 4.28 [95% confidence interval: 1.55-11.77], p=0.005, respectively). Conclusion: Total/mature cataract and the presence of any postoperative complication adversely affected the final BCVA. Having a congenital cataract and intraoperative anterior hyaloid membrane rupture increased the risk of complications.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Göz Hastalıkları ve Cerrahisi; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Eye Diseases and Surgery; Health Sciences; Klinik Tıp (MED); Klinik Tıp; GÖZ HASTALIKLARI; Clinical Medicine (MED); CLINICAL MEDICINE; OPHTHALMOLOGY; Oftalmoloji; Ophthalmology; complication; congenital cataract; developmental cataract; Pediatric cataract; surgery; visual outcomes